PENGARUH LATIHAN BOLA GLADIATOR TERHADAP KETEPATAN TENDANGAN (SHOOTING) PADA PEMAIN BOLA SSB MATADOR MARPOYAN DAMAI - Jasrizal Jasrizal; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT : The problem in this research is the lack of ability accuracy kick to score of the winner, this can be seen from the observation of researcher in this field the students that there are many SSB Matador Marpoyan Damai Pekanbaru their kick were not target. This research is experiment with using total sampling technique obtained a sample of 14 students. Instruments using in this research is a test shoot or kick the ball to a target aims to measure the accuracy of the kick. After that pre-test and handing practice ball gladiator during 16 sessions to 14 students SSB Matador Marpoyan Damai Pekanbaru and the continue with post test. The treatment data using statistical, to test normality with lilliefors test at significant level a=0,05. The hypothesis is the influence of practice ball gladiator toward the accuracy kick soccer players SSB Matador Marpoyan Damai Pekanbaru. Base on analysis statistical data, there are average of 10,43 in pre-test and post test average 12,86 then the data is normally distributed. Base on analysis test t result thuting as big as 6,613 > ttabel 1,771 of a=0,05, therefore can be concluded that there are influence of practice ball gladiator toward the accuracy kick in soccer players SSB Matador Marpoyan Damai Pekanbaru.Keywords: Ball gladiator, Accuracy Shooting